Defining sexual misconduct: power, media, and #MeToo - Hannem, Stacey (University of Regina Press, 2022)
"Defining Sexual Misconduct investigates shifts in media coverage of sexual violence and details significant changes in public discourse about sexual harm. In 2015, the New York Times ran just a single headline with the term “sexual misconduct.” Three years later, it ran dozens of such headlines, averaging more than one per week, and expanded coverage across other media organizations followed. This shift in coverage is reflective of significant changes in public discourse about sexual harm that has helped to hold some perpetrators accountable for their behaviour; it has also helped pave the path for #MeToo and related movements to garner national and global attention. In Defining Sexual Misconduct, Stacey Hannem and Christopher J. Schneider examine the contemporary dynamics of public accusations and their relationship to more formal criminal justice processes, as well as the implications for the stigmatization of alleged abusers and public response to alleged victims."--